ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DAN SISTEM INFORMASI PEMASARAN PADA INDUSTRI MEBEL DI DESA MOJOSONGO - Rosita .; Hestin Mutmainah; Ida Ayu Kade Rachmawati Kusasih (STIE AUB Surakarta, 2015)
Small industriesare seento able to survivethe currenteconomic crisisandto realize thepeople's welfare. Furniture centersin Mojosongo is a center of furniture in Central Java. This furniture centers face two major obstacles. They still use manual recording system and not well ordered. Marketing concepts that used are also still quite traditional, which only makes the products according to the availability of raw materials without see ing the desire ordem and. It requireda good Accounting Information Systems and Marketing Information System. Keywords: Accounting Information Systems, Marketing Information System.